Southern Species From the Biodiversity Hotspot of Central Chile: A Source of Color, Aroma, and Metabolites for Global Agriculture and Food Industry in a Scenario of Climate Change - Letelier, Luis; Gaete-Eastman, Carlos; Peñailillo, Patricio; Moya-León, María A.; Herrera, Raúl (Frontiers in Plant Science, 2020)
Two interesting plants within the Chilean flora (wild and crop species) can be found with a history related to modern fruticulture: Fragaria chiloensis subsp. chiloensis (Rosaceae) and Vasconcellea pubescens (Caricaceae). Both species have a wide natural distribution, which goes from the Andes mountains to the sea (East-West), and from the Atacama desert to the South of Chile (North-South). The growing locations are included within the Chilean Winter Rainfall-Valdivian Forest hotspot. Global warming is of great concern as it increases the risk of losing wild plant species, but at the same time, gives a chance for usually longer term genetic improvement using naturally adapted material and the source for generating healthy foods. Modern agriculture intensifies the attractiveness of native undomesticated species as a way to provide compounds like antioxidants or tolerant plants for climate change scenario. F. chiloensis subsp. chiloensis as the mother of commercial strawberry (Fragaria × ananassa) is an interesting genetic source for the improvement of fruit flavor and stress tolerance. On the other hand, V. pubescens produces fruit with high level of antioxidants and proteolytic enzymes of interest to the food industry. The current review compiles the botanical, physiological and phytochemical description of F. chiloensis subsp. chiloensis and V. pubescens, highlighting their potential as functional foods and as source of compounds with several applications in the pharmaceutical, biotechnological and food science. The impact of global warming scenario on the distribution of the species is also discussed.